Penerapan Sistem Informasi Akuntansi Pada Perusahaan PT Hi Rembulan - Alya Putri Desryadhi; Emiliana Putri; Risma Mutiara (Jurnal Akuntan Publik, 2025)
The purpose of this research is to find answers to what the accounting information system is regarding inventory, cash sales and cash receipts at the Hi.Rembulan company. Can be refined according to a good and theoretically correct accounting information system for inventory, cash sales and cash receipts, so that it can be applied according to company conditions. The rationale for this research is the need to implement an accounting information system regarding inventory, cash sales and cash receipts at the Hi.Rembulan company. Then analyze the weaknesses in the company. So that alternative solutions to problems that arise can be created in accordance with a good and theoretically correct accounting information system. From the results of this research, it is concluded that in solving the problem of implementing an accounting information system regarding inventory, cash sales and cash receipts, it is best to strictly separate responsibilities and carry out accounting functions by different people to avoid cash misappropriation, the documents used are such as notes. Sales are printed serial numbers so that use can be accounted for by the authorized user of the document.